2004
DOI: 10.1007/s10162-004-4044-3
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Eya1 and Eya4 Protein Function and Its Implication in Branchio-oto-renal Syndrome and DFNA10

Abstract: Allele variants of EYA1 and EYA4, two members of the vertebrate Eya gene family, underlie two types of inherited human deafness, branchio-oto-renal (BOR) syndrome and DFNA10, respectively. To clarify how mutations in these two genes and their encoded proteins impact the normal biology of hearing, we completed a number of functional studies using the yeast-two-hybrid system. We verified that bait constructs of the homologous region (Eya1HR and Eya4HR) interact with Six1 prey constructs, although no interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 22 publications
0
47
0
1
Order By: Relevance
“…Eya1 and Six1 have been studied extensively and play a role in the formation of most placode derivatives (see below), reflecting their widespread expression in the preplacodal region. Likewise, mutations in Eya4 and Six5 are associated with defects in placode derivatives (Klesert, et al, 2000;Wayne, et al, 2001;Zhang, et al, 2004), while information about Six2 and Eya2 is very sparse. Mice lacking Eya2 function have been generated, however, their placodal phenotype has not been described in detail (Grifone, et al, 2007).…”
Section: Six and Eya Genes In Sensory Organ Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Eya1 and Six1 have been studied extensively and play a role in the formation of most placode derivatives (see below), reflecting their widespread expression in the preplacodal region. Likewise, mutations in Eya4 and Six5 are associated with defects in placode derivatives (Klesert, et al, 2000;Wayne, et al, 2001;Zhang, et al, 2004), while information about Six2 and Eya2 is very sparse. Mice lacking Eya2 function have been generated, however, their placodal phenotype has not been described in detail (Grifone, et al, 2007).…”
Section: Six and Eya Genes In Sensory Organ Formationmentioning
confidence: 99%
“…Eya1 mutations in humans are also associated with congenital eye defects (Azuma, et al, 2000), although these have not been described in mice. Finally, mutations in the eya-homologous region of Eya4 lead to late-onset deafness in humans (Wayne, et al, 2001;Zhang, et al, 2004;Schonberger, et al, 2005).…”
Section: Six and Eya Genes In Sensory Organ Formationmentioning
confidence: 99%
“…However, studies of vertebrate Eya1-4 in cultured cells have revealed that these proteins localize to the cytoplasm and require cotransfection with Six1/2 or Six4/5 subfamilies to accumulate stably in the nucleus (24,119). Intracellular localization of the vertebrate Eya homologs in the presence and absence of Six family proteins in whole animals has not been reported.…”
Section: Eya Subcellular Localizationmentioning
confidence: 99%
“…Likewise, Pax7 and Eya4 share significantly similar developmental expression patterns; both play critical roles in neurogenesis and myogenesis and are highly expressed in developing brain, craniofacial mesenchyme, dermomyotome and limb during embryogenesis (6,25,49), and both Eya4 and Pax7 are robustly expressed in brain and skeletal muscle in adult mouse tissues (65,70,82). Eya family members function as transcriptional coactivators controlling cell fate specification, cell survival and apoptosis, proliferation, differentiation, and morphogenesis (34,49,57).…”
Section: Discussionmentioning
confidence: 99%